KEARIFAN LOKAL NELAYAN SUKU AKIT DI DESA TANJUNG KEDABU KECAMATAN RANGSANG PESISIR KABUPATEN KEPULAUAN MERANTI - Andini, Fitri; Jalil, Ashaluddin; Resdati, Resdati (Jurnal Pendidikan Sosiologi dan Humaniora, 2022)
This Study aims to determine the forms of local wisdom of the Akit Tribe fishermen and to find out equipment the Akit tribe fishermen use to catch fish in the Rangsang Pesisir District.The research method used is a qualitative method. Data were collected by observation and in-depth interviews, in addition to of course documentation. The results of the study found that there are several forms of local wisdom related to the activities of fishermen that still exist and live and are used in the life of the fishermen community. The local wisdom referred to include: First, the Bele Laut Ritual, which is an activity that aims to maintain or keep the sea still providing sustenance and safety for fishermen. The second ritual of getting off the boat is when buying a new boat is done as a form of gratitude for the fishermen for the new boat. Third, Determination of time, weather and seasons, the fishermen of the Akit Tribe believe in natural signs, such as when there are many stars at night, tomorrow the weather will be shady and sunny. Then they believed that the cloud that was scaly like fish in the afternoon was a sign that it was fish season.   The meaning of maintaining ecology is when going to sea (netting, splinting) when the catches obtained by fishermen sort the fish, meaning that small fish that are considered unable or less useful are released into the sea. This clearly means that they have thought about the sustainability of animal life (sea) for the future or for their children and grandchildren who will become fishermen. The fishing activities of the Akit Tribe still use simple technology and equipment such as motorboats, oars and nets.